Pelatihan Keterampilan Numerasi Peserta Didik di SMPN 1 Plumbon Menuju Sekolah Siaga Kependudukan - Wulandari, Hesty Ummi; Wati, Hesty Marliana; Pramesti, Ervita Dian; Nurcholisyah, Ela; Jumaesari, Efi; Arwanto, Arwanto; Nurlaela, Nurlaela (Institut Agama Islam Negeri Kerinci, 2025)
Numeracy skills are important skills for students in helping students solve everyday problems and support decision-making based on data and mathematical logic. Numeracy skills are integrated with everyday problems such as population. This study aims to train students' numeracy skills through training integrated with population issues, especially nutritional status based on Body Mass Index (BMI). This training activity was carried out at SMPN 1 Plumbon with 30 IPS and PMR extracurricular students. The training activity went through three stages, namely the planning, implementation and evaluation stages. The planning stage is the team coordinating with the supervising teacher regarding the training concept and creating materials. The implementation stage is carried out twice, namely the presentation of materials by the resource person and the practice of calculating BMI using the Microsoft Excel application. The evaluation stage is to help students interpret the results of data processing in the form of infographics.